Europe Inc. : regional and global restructuring and the rise of corporate power. - Balanyá, Belén; Corporate Europe Observatory (CEO); Doherty, Ann; Hoedeman, Olivier; Ma'anit, Adam; Wesselius, Erik (London : Pluto Press, 2000)
Bibliotheek François Vercammen
Engels
Monografie